Impact of the COVID-19 pandemic on religious tourism amongst Muslims in Iraq - Prasetio, Arif Partono (HTS teologiese studies, 2022)
Tourism, as an industry, has become one of the most dynamic sectors of the world economy these days and has specific features that are different from other industries. In the tourism industry, production and consumption points occur spatially at the same time. In addition, the tourism industry contributes to the economic growth of developed regions and can simultaneously distribute the wealth created geographically. It is notable that the coronavirus disease 2019 (COVID-19) pandemic has caused many challenges in the tourism industry regarding the presence of tourists in tourism centres and the closing of all tourism service chains, including food, entertainment, transportation and travel services worldwide. Tourism-related businesses, which are considered as invisible export and one of the engines of development and occupation, have been rendered obsolete. In other words, the businesses, as well as multiple units and activities in the related chain, have been damaged and employees of this industry have lost their jobs. This has led to the recession and regressive course of the developing and large industry of tourism in the world. It is worth noting that the tourism industry includes various sections, the most important of which is religious tourism. All religions in the world have different religious places, works, traditions and customs, which have become amongst the most important tourist attractions. Meanwhile, Muslims and the religion of Islam play a significant role in this branch of tourism. The Hajj, pilgrimage to holy places and the existence of mourning ceremonies or religious celebrations of Muslims are amongst the largest religious tourism events in the world. Given the importance of this issue, the present study aimed to evaluate the impact of the COVID-19 pandemic on religious tourism in Iraq in 2021. This field study was conducted on 4500 Muslim managers and staff of restaurants, hotels, grocery stores, clothing stores and souvenir shops around the holy shrines of imams and religious places in Karbala, Najaf, Kufa, Samarra and Kazemi. According to the results, the tourism of Iraq, which is mainly limited to Muslim religious sites in several major Iraqi cities, has also seen a decline in the number of religious tourists. The negative effects of COVID-19 on religious tourism have also been proved statistically by the Statistical Package for the Social Sciences (SPSS), as µ ≥ 3 has been counted in all indices.Contribution: Our findings offered new insights into the impact of COVID-19 on tourism, based on statistical analysis. In this study, the authors showed how COVID-19 affects various aspects of religious tourism, which has not been addressed in previous researches.